The Influence of Departure Waiting Room Facilities on Passenger Satisfaction at Yogyakarta International Airport - Khasan, Ilham Nur (Formosa Journal of Sustainable Research, 2024)
Yogyakarta International Airport with IATA code: YIA and ICAO code: WAHI is an airport in Kulon Progo, Yogyakarta. which is used for civil aviation. The purpose of this study was to find and analyze whether there is an influence of waiting room facilities on passenger satisfaction. This study uses an associative method with a quantitative approach, and data were collected through questionnaires. The respondents of this study were users of the waiting room at Yogyakarta International Airport. The results of the study are presented with a simple linear regression analysis. According to the t test, there is a positive and significant relationship between passenger satisfaction (Y) and waiting room facilities (X); the result is Y = -4.524 + 1.478 X and the correlation coefficient R = 0.881. is 77.7%, and other factors affect 22.3%